Strengthening The Characters of Love for The Country Trough Civic Education of Students in School Based on Pesantren - Teguh Faisal Muchayat; Aim Abdulkarim; Dadang Sundawa (Jurnal Civicus, 2020)
Facing the era of globalization and modernization in this very dynamic era, researchers believe in the importance of strengthening the character of love for the country in students as the nation's next generation, one way is through Civic Education. Because Civic Education aims to prepare the next generation with a personality, culture and national perspective. By preparing the next generation who have a spirit of nationalism and a good national insight, this can be said to be a long-term plan for the continuity of the Indonesian nation and state in the future, because they are the ones who will continue leadership in this country and are responsible for maintaining unity and national unity and the ideology of Pancasila as the life guide for every Indonesian citizen in the future. Fostering a sense of patriotism or nationalistic values in the nation's future generations, which is one way through Civic Education, which is the most appropriate answer in facing the challenges of today's era and modernization. Because these efforts are very important and fundamental, so that the future generations of the nation can implement or practice the values of nationalism and Pancasila in their daily lives.